Linking the Tourism Activity to the Occurrence and Distribution of Microplastics - Chairunnisa, Nadda Khalila; Adam, Moh. Awaludin; Kristianto, Sonny; Aidil Candri, Dining; Shofi Talbia, Husna; Aprilia, Maya; Mutia, Tuti; Masruroh, Heni; Iswara, Aditya Prana; Prayogo, Wisnu (Civil Engineering Journal, 2025)
Tourism-driven activities have increasingly contributed to marine microplastic (MPs) pollution, particularly in island ecosystems. This study assesses the abundance, characteristics, and spatial distribution of MPs in Gili Trawangan, Indonesia, by analyzing samples from coastal water, sediments, and fish across three zones: a seaport, recreational beach, and mangrove area. Standardized filtration, density separation, and FTIR spectroscopy were used to identify MPs types and polymers. Results show the highest MPs concentrations in coastal water at recreational beaches (19.25 particles/L), sediment at seaports (23.15 particles/kg), and fish near seaports (17.5 particles/individual), indicating elevated risks of bioaccumulation. Fragments and fibers were the dominant forms, with prevalent polymers including PS, PE, and LDPE, mostly in black, blue, and red colors. The mangrove area exhibited lower MPs levels due to its natural filtration capacity but still showed MPs presence in biota. This multi-compartment approach highlights a clear link between tourism intensity and MPs contamination. The findings provide new insights for designing localized interventions, including waste reduction strategies and regulatory measures. By integrating ecological and anthropogenic factors, this study supports the development of sustainable tourism policies to mitigate MPs pollution and protect coastal biodiversity.